Analisa Sebaran Genangan Banjir Akibat Keruntuhan Bendungan Tempuran - Waryani, Retno Sri; Sachro, Sri Sangkawati; Edhisono, Sutarto (Department of Civil Engineering, Diponegoro University, 2025)
The Tempuran Dam is one of the oldest dams in Indonesia and is currently experiencing a lot of damage, which could potentially lead to dam failure such as a dam collapse. To reduce the impact of losses resulting from dam collapses, it is necessary to analyze flood inundation patterns in the context of disaster mitigation. The dam failure analysis was modeled using HEC-RAS software with failure conditions due to overtopping and due to piping. The input in this modeling is the PMF plan discharge which is generated using HEC-HMS modeling with the HSS SCS method. The data required for HEC-HMS modeling are raster maps, land use maps, soil type maps and Hersfield method PMP rainfall plans. From the analysis results, it was found that the PMF planned flood was 115.54 m3/sec. The area of the flood inundation due to the collapse of the Tempuran Dam, the bottom piping condition was 2.61 km2 and the depth of the flood varied between 0 m to 3 m, where the area most deeply affected by the inundation was Purwosari Village, Blora Kota District. From the mapping results, the areas affected by flood inundation due to the collapse of the Tempuran Dam are Tempuran Village, Sendangharjo Village, Ngadipurwo Village, Purwosari Village, Patalan Village and Tempurejo Village. Where the fastest flood travel time is 48 minutes to Tempuran Village and the longest flood travel time is 5.25 hours to Tempurejo Village.